2004
DOI: 10.1111/j.1600-0447.2004.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Amisulpride augmentation of clozapine: an open non‐randomized study in patients with schizophrenia partially responsive to clozapine

Abstract: Co-administration of amisulpride, in a group of patients partially or non-responsive to clozapine, may lead to a substantial improvement in positive and negative symptoms, without worsening the side effect burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 30 publications
5
36
0
3
Order By: Relevance
“…Patients scoring 25 or more on the Brief Psychiatric Rating Scale (Overall and Gorham, 1962) at the baseline evaluation were classified as partial-responders or non-responders to clozapine (Munro et al, 2004). The patients' age, gender and duration of illness are shown in Table 1.…”
Section: Subjectsmentioning
confidence: 99%
“…Patients scoring 25 or more on the Brief Psychiatric Rating Scale (Overall and Gorham, 1962) at the baseline evaluation were classified as partial-responders or non-responders to clozapine (Munro et al, 2004). The patients' age, gender and duration of illness are shown in Table 1.…”
Section: Subjectsmentioning
confidence: 99%
“…51 We identified nine noncontrolled observational trials comparing antipsychotic polypharmacy to monotherapy in samples with established treatment resistance to trials of a single antipsychotic (Table 1). [53][54][55][56][57][58][59][60][61] All studies were of patients with schizophrenia or schizoaffective disorder. Eight of the trials reported significant improvement in reduced symptoms with the addition of a second antipsychotic.…”
Section: Samples With Established Treatment Resistance To Antipsychotmentioning
confidence: 99%
“…53,[55][56][57][58][59][60][61] Of the eight studies that examined side effects, four reported no change with the addition of a concurrent antipsychotic. 53,54,59,60 Three studies reported increased side effects with the addition of another antipsychotic, [56][57][58] whereas one study reported a decrease in sedation. 56 The observational studies also had small sample sizes (7-28 patients), and most of them were longer than the RCTs (1-9 months).…”
Section: Samples With Established Treatment Resistance To Antipsychotmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, aripiprazole aside, these add-on therapies were associated with lower tolerability. Another option is augmentation with amisulpride, 5,6 which has been reported to be effective and well tolerated.…”
mentioning
confidence: 99%